Current Account Rebalancing and Real Exchange Rate Adjustment Between the U.S. and Emerging Asia - Sandri, Damiano (IMF Working Papers; Working Paper, 2011)
A reduction in the U.S. current account deficit vis-a-vis emerging Asia involves a shift in demand from U.S. to emerging Asia tradable goods and a change in international relative prices. This paper quantifies the required adjustment in the terms of trade and real exchange rates in a three-country open economy model of the U.S., China, and other emerging Asia. We compare scenarios where both Chinese and other emerging Asian export prices change by the same proportion to the case where export prices remain constant in one country and increase in the other. Our results are robust to different assumptions about elasticities of substitution and to introducing a high degree of vertical fragmentation in production in the model.